The obstacles of applying the evaluation of teaching My Eternal Language Course of the intermediate stage from the point of view of teachers and principals - Al Dawood, Badr bin Abdul Aziz (Arab Journal for Sciences and Research Publishing, 2016)
Objective of the study: To identify the obstacles to the application of the evaluation related to teacher, student, and content, from the point of view of teachers and principals, and to identify whether there are differences of statistical significance between the average views of teachers and principals.The researcher used the descriptive descriptive method and applied a questionnaire consisting of (35) words in the fields of study distributed in two axes. After verifying the validity of the tool, it was applied to the study community consisting of (14) principals and (35) teachers. Results: The existence of obstacles to the calendar in the course of my immortal language related to the student to a large extent, and an average of (3.73 of 5.00), the most important of these obstacles: lack of cooperation with the school in the follow-up of the results of the calendar, and the lack of self-reliance on the student, , And an average of (3.51 of 5.00). The most important of these obstacles: the lack of training of teachers on the use of methods of assessment, increase the quorum of the teacher, and the different standards from one teacher to another, as well as the existence of obstacles related to the content to a large extent, and an average (3.96 of 5.00) Content, lack of interest in spelling and grammatical skills, and the abundance of activities and training Which has no relation to Arabic. The study revealed that there were statistically significant differences at the level of (0.05) and less among the study community of teachers and principals in favor of teachers. Conclusion: There are obstacles in the application of the calendar to the decision of my immortal language in the middle stage related to the student and teacher and content.
Keywords: Calendar Obstacles; My Timeless Language for the Middle School; Saudi Arabia